Samoocena stanu zdrowia i jej wybrane uwarunkowania w grupie osób po 65 roku życia, pacjentów Podstawowej Opieki Zdrowotnej = The self-assessment of health and its selected conditions within a group of over-65-year-old primary-care patients - Nowicki, Grzegorz Józef; Młynarska, Magdalena; Ślusarska, Barbara; Korecka, Renata; Kotus, Marzena (Journal of Education, Health and Sport, 2016)
Nowicki Grzegorz Józef, Młynarska Magdalena, Ślusarska Barbara, Korecka Renata, Kotus Marzena. Samoocena stanu zdrowia i jej wybrane uwarunkowania w grupie osób po 65 roku życia, pacjentów Podstawowej Opieki Zdrowotnej = The self-assessment of health and its selected conditions within a group of over-65-year-old primary-care patients. Journal of Education, Health and Sport. 2016;6(4):447-457. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.50611 http://ojs.ukw.edu.pl/index.php/johs/article/view/3492 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.04.2016. Revised 25.04.2016. Accepted: 27.04.2016. Samoocena stanu zdrowia i jej wybrane uwarunkowania w grupie osób po 65 roku życia, pacjentów Podstawowej Opieki Zdrowotnej The self-assessment of health and its selected conditions within a group of over-65-year-old primary-care patients Grzegorz Józef Nowicki1, Magdalena Młynarska2, Barbara Ślusarska1, Renata Korecka2, Marzena Kotus3 1. Zakład Medycyny Rodzinnej i Pielęgniarstwa Środowiskowego, Katedra Onkologii i Środowiskowej Opieki Zdrowotnej, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie 2. Zakład Ratownictwa Medycznego, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie 3. Zakład Pielęgniarstwa Anestezjologicznego i Intensywnej Opieki Medycznej, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie Słowa klucze: samoocena stanu zdrowia, osoby starsze, podstawowa opieka zdrowotna. Key words: self-assessment of health, the elderly, primary health care. Streszczenie Wprowadzenie. Starzenie się jest procesem stałym, będącym poważnym wyzwaniem dla społeczeństwa. Współcześnie maksymalizuje się wysiłki w celu przedłużenia życia w sensie biologicznym, ale również po to, aby przybliżyć poziom jakości życia do stanu sprzed choroby. Uznano, że bardzo istotne w procesie leczenia i pielęgnowania pacjenta jest samoocena własnego zdrowia. Pozwala to na aktywne włączenie chorego w realizację procesów terapeutycznych, co jest korzystne zarówno dla pacjenta, jak i dla zespołu leczącego. Cel. Poznanie samooceny stanu zdrowia i jej uwarunkowań w grupie osób powyżej 65 roku życia, pacjentów Podstawowej Opieki Zdrowotnej. Materiał i metoda. Badania przeprowadzono od lipca do września 2013 r. wśród 505 osób w wieku powyżej 65 roku życia w losowo wybranych 5 jednostkach Podstawowej Opieki Zdrowotnej (POZ) na terenie województwa lubelskiego. Narzędziem badawczym był autorski kwestionariusz ankiety. Wyniki. W samoocenie stanu zdrowia badani w większości określili swoje zdrowia jako złe (odpowiedzi zły i bardzo zły) – 214 (42,38%). Ci, którzy zadeklarowali, że ich stan zdrowia jest przyzwoity stanowią drugą pod względem liczności grupę – 167 (33,07%). Jedynie 124 osoby (24,56%) zadeklarowały, że ich zdrowie jest dobre lub bardzo dobre. Analiza statystyczna wykazała, że swój stan zdrowia istotnie częściej lepiej oceniają: badani w wieku 76 - 85 lat (p=0,007), posiadający wykształcenie podstawowe, zawodowe, średnie, wyższe (p<0,001) w porównaniu do badanych nie posiadających wykształcenia, osoby znajdujące się w związkach partnerskich lub konkubinacie (p=0,001), nie posiadające problemów finansowych (p<0,001), nie odczuwające bólu (p<0,01) oraz nie posiadające ograniczeń w sprawności fizycznej (p<0,001). Badani wykonujący w przeszłości zawód związany z praca fizyczną istotnie gorzej oceniają swój stan zdrowia (p=0,001). Wnioski. Analiza samooceny stanu zdrowia pozwala stwierdzić, żewiększość uczestników badania nie cieszy się dobrym zdrowiem. Wykazano, że samoocena stanu zdrowia zależy od: wieku, wykształcenia, stanu cywilnego, statusu finansowego, odczuwania bólu, sprawności fizycznej oraz charakteru zawodu wykonywanego w przeszłości. Abstract Introduction. Ageing is a constant process which constitutes a serious challenge to society. Today every effort is maximised in order to extend human life in the biological sense, and also to come as close as possible to the pre-disease quality of life. It is maintained that health self-assessment is a very important measure in the process of the treatment and nursing of the patient. It allows the patient to be actively included in the implementation of therapeutic processes, which is advantageous for both the patient and the treating team. Purpose. The knowledge of health self-assessment and its conditions within a group of over-65-year-old primary-care patients. Materials and methods. The research was conducted from July to September 2013 among 505 people aged over 65 at 5 randomly selected primary care units (POZ) on the territory of the Lubelskie Voivodeship. The research tool used in this paper was a questionnaire devised by the author. Results. During health self-assessment most patients defined their state of health as poor (answers: poor and very poor – 214 (42.38%)). Those who claimed to maintain a decent level of health constituted the second largest group of respondents – 167 (33.07%). Only 124 persons (24.56%) described their health as good or very good. The statistical analysis showed that the following groups considerably more frequently assess their health as better: the survey participants aged 76-85 (p=0.007) with primary, vocational, secondary and higher education (p<0.001) (compared to subjects without education), people in civil unions or domestic partnerships (p=0.001), patients without financial problems (p<0.001) and those who don’t feel pain (p<0.01), as well as people without physical limitations (p<0.001). The examined persons who had performed physical work in the past described their state of health as significantly worse (p=0.001). Conclusions. The analysis of health self-assessment allows us to conclude that most of the survey participants do not enjoy good health. It has been shown that the results of health self-assessment depend on the following factors: age, education, civil status, financial status, feeling pain, physical fitness and the nature of work performed in the past.